2017
DOI: 10.18203/2320-1770.ijrcog20175847
|View full text |Cite
|
Sign up to set email alerts
|

VIA (Visual inspection with acetic acid) and VILI (Visual inspection with lugol’s iodine) as an initial approach with colposcopy as a next screening tool with its positive predictive value in low socioeconomic patients

Abstract: Background: Cervical Cancer is the second most common cancer in women worldwide and India alone contribute the 1/4th of the world’s cases of cervical cancer. In view to this huge burden there was need to establish a feasible screening programme to detect cervical carcinoma at earliest in developing country.Methods: This is a prospective study of 500 women who fulfil the selection criteria. 50 pregnant patients for VIA (Visual inspection with acetic acid), 50 pregnant patients for VILI (Visual inspection with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(12 reference statements)
3
4
0
Order By: Relevance
“…This was comparable to studies by Goldacre et al, Paswan et al, Bhalerao et al and Garg et al where the most common presenting complaint was consistently vaginal discharge which may or may not be associated with lower backache. [6][7][8][9] In a study by Dasari et al unhealthy vaginal discharge was observed in 13.3% patients which was comparable to 25% patients presenting with unhealthy vaginal discharge in the present study. 10 This increased incidence of unhealthy vaginal discharge may be attributed to the increased prevalence of lower socioeconomic strata and poor personal hygiene in our study group.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…This was comparable to studies by Goldacre et al, Paswan et al, Bhalerao et al and Garg et al where the most common presenting complaint was consistently vaginal discharge which may or may not be associated with lower backache. [6][7][8][9] In a study by Dasari et al unhealthy vaginal discharge was observed in 13.3% patients which was comparable to 25% patients presenting with unhealthy vaginal discharge in the present study. 10 This increased incidence of unhealthy vaginal discharge may be attributed to the increased prevalence of lower socioeconomic strata and poor personal hygiene in our study group.…”
Section: Resultssupporting
confidence: 82%
“…It was comparable to the study by Sharma et al and Pankaj et al in which the most common age group was 31-40 years. The mean parity in the present study was 2.78±1.39 which was comparable to the studies by Sharma et al, Paswan et al and Bhalerao et al[4][5][6][7] The most common presenting complaint in this study was vaginal discharge as seen in 68.8% patients. This was comparable to studies by Goldacre et al, Paswan et al, Bhalerao et al and Garg et al where the most common presenting complaint was consistently vaginal discharge which may or may not be associated with lower backache [6][7][8][9].…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Visual inspection with acetic acid (VIA) and visual inspection with Lugol's iodine (VILI) are increasingly recommended in various cervical cancer screening protocols in low-resource settings; although VIA is more widely used, VILI has been advocated as an easier and more specific screening test (Huchko et al, 2015). In many developing countries where pap smear and colposcopy are not available, both VIA and VILI remain very helpful tools in picking up abnormal-looking cervix which can then be confirmed by pap smear or colposcopy especially among individuals at high risk of cervical cancer such as WLHIV (Paswan et al, 2018). It's expected that screening using any of the two methods can go a long way in reducing the incidence of cervical carcinoma among HIV-positive women.…”
Section: Introductionmentioning
confidence: 99%